Lebanon - Second Education Development Project - World Bank (Washington, DC World Bank, 2010)
The article examines a second phase of education reform based on the Education Sector Development Plan, with a focus on quality learning for growth at the preschool, primary and secondary education levels. Essentially, this Plan aims at modernizing the public education sector in Lebanon, thus leveling the playing field between the private and public sectors, and building the capacity of the Ministry of Education and Higher Education to effectively manage the whole education system and to make evidence-based policy decisions. The Government of Lebanon has requested the World Bank to support this Education Sector Development Plan with this objective, both financially and technically. This operation is a Sector Investment Loan (SIL), financed by an IBRD Loan in the amount of US
: Report
Keywords: Educational policy; Politique éducative